Human haematological and epithelial tumor-derived cell lines express distinct patterns of onco-microRNAs - Biamonte, Flavia; Zolea, Fabiana; Santamaria, Gianluca; Battaglia, Anna M.; Cuda, Giovanni; Costanzo, Francesco (Cellular and Molecular Biology, 2017)
MicroRNAs post-transcriptionally regulate gene expression thus playing a critical role in a wide range of physiological and pathological processes, including cancer initiation and progression. Moreover, a growing number of evidences highlights that miRNAs themselves are differentially expressed between normal and malignant tissues. In this study, we analysed differences in miRNA expression profile between haematological and epithelial tumor-derived cell lines and explored their role in definying different cancer cells phenotypes. Cancer Focus microRNA PCR Panel was used to analyze eighty-four oncomiRNAs in two human haematological (K562 and HL-60) and in two epithelial (H460 and MCF-7) cancer cell lines. Bioinformatic tools were used to identify miRNA-specific signatures and to discover potentially deregulated pathways. Our analysis led to the identification of i) a large repertoire of miRNAs commonly expressed in the four cell lines, including two equally highly expressed (UPmiRs) and four equally low expressed (DNmiRs); ii) two miRNAs signatures, one associated with the haematological and one with the epithelial cell lines; iii) miRNA signatures specific for the acute or for the chronic myeloid leukemic cells; iv) miRNA signatures specific for the lung or for the breast carcinoma cells. As a whole, these results strengthen the significance of miRNAs profiling in human cancer subtyping, providing the ground for the identification of novel potential biomarkers for specific cancer cell phenotypes.